Transition Towards Accrual Accounting and Disclosure Requirements in the Malaysian Public Sector: A Case of Sarawak - Junaidi, Hadysyam (Curtin University, 2018)
Drawing from the institutional theory and the Ouda’s (2010) Prescriptive Model, this study examines the disclosure requirements for the transition towards accrual accounting in the Malaysian public sector, by taking a case of Sarawak local authorities (SLA). The study demonstrates that there is a low level of accrual disclosure in the SLA’s annual financial statements. In conclusion, the accrual implementation would require a comprehensive transition framework available for the reference of the SLA.